Potential of IoT in Healthcare Systems: A Review - Khushdeep Kaur (International Journal of Advanced Science and Technology, 2020)
IoT is a technology that is basically a system of computing devices that are interrelated, digital or mechanical machines, objects, animals or people that have unique identifiers and also have the ability of data transfer over a network without any human-to-human or human-to-computer intercommunication while conventional internet expedites communications as stated above. When IoT is used with medical devices not beyond a connected health environment allows for rapid information flow as well as facile access to it, provides provision of ubiquitous health monitoring and emergency response services etc. Internet of Things (IoT) has the capability to hinder the procreation of COVID-19 alike outbreaks and can be utilized for implementation in the future to not to face such health exigencies. This paper analyzes the potential of IoT and its various segments, applications in the field of healthcare. Light has also been thrown on the different current developments in IoT and cloud computing based applications in healthcare used specifically by developed countries to contain COVID-19